Clustering of low-mass stars around Herbig Be star IL Cep – evidence of 'Rocket Effect' using Gaia EDR3 ?. Issue 1 (21st July 2021) - Arun, R; Mathew, Blesson; Maheswar, G; Baug, Tapas; Kartha, Sreeja S; Selvakumar, G; Manoj, P; Shridharan, B; Anusha, R; Narang, Mayank
ABSTRACT: We study the formation and the kinematic evolution of the early-type Herbig Be star IL Cep and its environment. The young star is a member of the Cep OB3 association, at a distance of 798 ± 9 pc, and has a 'cavity' associated with it. We found that the B0V star HD 216658, which is astrometrically associated with IL Cep, is at the centre of the cavity. From the evaluation of various pressure components created by HD 216658, it is established that the star is capable of creating the cavity. We identified 79 co-moving stars of IL Cep at 2-pc radius from the analysis of Gaia EDR3 astrometry. The transverse velocity analysis of the co-moving stars shows that they belong to two different populations associated with IL Cep and HD 216658, respectively. Further analysis confirms that all the stars in the IL Cep population are mostly coeval (∼0.1 Myr). Infrared photometry revealed that there are 26 Class II objects among the co-moving stars. The stars without circumstellar disc (Class III) are 65 per cent of all the co-moving stars. There are nine intense H  α emission candidates identified among the co-moving stars using IPHAS H  α narrow-band photometry. The dendrogram analysis on the Hydrogen column density map identified 11 molecular clump structures on the expanding cavity around IL Cep, making it an active star-forming region. The formation of the IL Cep stellar group due to the 'rocket effect' by HD 216658 is discussed.